Cross-Modality Generalization in Reading and Spelling Instruction. Issue 4 (1st December 2017) - Miller, Sarah J.; Noell, George H.; McIver, Elise C.; Lark, Catherine R.
Abstract: Reading and spelling are essential skills for educational success. Spelling instruction research has examined varied modalities but has never directly compared written versus oral spelling. Theoretical and empirical indications exist that either method may be superior to the other. Study 1 compared written and oral spelling instruction for rates of spelling acquisition and generalization to reading. Results indicated written spelling instruction resulted in more rapid acquisition of spelling and reading accuracy compared to oral spelling instruction. Previous research has demonstrated cross-modality generalization can occur between reading and spelling (Noell, Connell, & Duhon, 2006 ); however, methodological issues limited these investigations. Study 2 compared reading instruction alone, spelling instruction alone, and combined reading and spelling instruction while controlling for instructional time. Results indicated that combined instruction led to the most rapid acquisition of spelling and reading accuracy. These findings are discussed in relation to behavioral concepts such as stimulus control and generalization.